The real, the imaginary, and the symbolic : a lacanian reading of Ramita Navai’s City of Lies - Nurfarah Hadira Abdul Hadi; Asl, Moussa Pourya (Penerbit Universiti Kebangsaan Malaysia, 2022)
Contemporary life writings of Iranian diaspora are often censured for promoting a universalizing, dehumanizing and hegemonic image of the nation. The common misgiving is that the narratives project Iranian women as archetypal victims and their male counterparts as essentially powerful subjects. The present study aims at problematizing this assumption by arguing that Ramita Navai’s City of Lies (2014) portrays an anti-essentialist character sketch of individuals with diverse identities and complex subjectivities. To pursue this line of argument, this article examines the titular characters’ development in the face of the existing tensions between the different psychic and social realities. Lacan’s triadic model of the Real, the Imaginary, and the Symbolic is used in relation to his notion of the mirror stage to analyze the ways in which the characters traverse between the three orders in the process of forming a sense of selfhood. The notion of selfhood is explored in light of latent desires, anxieties, and the feelings of loss as determining factors behind the psychic development of each character within the prevailing normativities of a heteropatriarchal government. The findings reveal that while Amir, Leyla, Asghar, Bijan, and Farideh find themselves permanently lost in the unconscious tensions between different psychic orders. Dariush, Morteza, and Somayeh break into the Symbolic order and reassert their subjectivity. In this manner, the life writing challenges the grand narratives about Iranians as a homogenous group of people as it offers an equal chance of attaining selfhood and subjectivity to both male and female characters.